Absolute Reliability of Hamstring to Quadriceps Strength Imbalance Ratios Calculated Using Peak Torque, Joint Angle-Specific Torque and Joint ROM-Specific Torque Values - Ayala, F.; De Ste Croix, M.; Sainz de Baranda, P.; Santonja, F. (International Journal of Sports Medicine, 2012)
The main purpose of this study was to determine the absolute reliability of conventional (H/QCONV) and functional (H/QFUNC) hamstring to quadriceps strength imbalance ratios calculated using peak torque values, 3 different joint angle-specific torque values (10°, 20° and 30° of knee flexion) and 4 different joint ROM-specific average torque values (0–10°, 11–20°, 21–30° and 0–30° of knee flexion) adopting a prone position in recreational athletes. A total of 50 recreational athletes completed the study. H/QCONV and H/QFUNC ratios were recorded at 3 different angular velocities (60, 180 and 240°/s) on 3 different occasions with a 72–96 h rest interval between consecutive testing sessions. Absolute reliability was examined through typical percentage error (CVTE), percentage change in the mean (CM) and intraclass correlations (ICC) as well as their respective confidence limits. H/QCONV and H/QFUNC ratios calculated using peak torque values showed moderate reliability values, with CM scores lower than 2.5%, CVTE values ranging from 16 to 20% and ICC values ranging from 0.3 to 0.7. However, poor absolute reliability scores were shown for H/QCONV and H/QFUNC ratios calculated using joint angle-specific torque values and joint ROM-specific average torque values, especially for H/QFUNC ratios (CM: 1–23%; CVTE: 22–94%; ICC: 0.1–0.7). Therefore, the present study suggests that the CVTE values reported for H/QCONV and H/QFUNC (≈18%) calculated using peak torque values may be sensitive enough to detect large changes usually observed after rehabilitation programmes but not acceptable to examine the effect of preventitive training programmes in healthy individuals. The clinical reliability of hamstring to quadriceps strength ratios calculated using joint angle-specific torque values and joint ROM-specific average torque values are questioned and should be re-evaluated in future research studies.
Keywords: reproducibility; dynamic knee stability; measurement error; injury; torque; isokinetic